Propuesta y diseño de espacios recreativos en las riberas del río Chamba de la parroquia Vilcabamba, cantón Loja. - Castro Bravo, Johanna Elizabeth (2014)
The Chamba River is located in Vilcabamba belonging to the Loja city. This research project is about scenically rescue the riverside, providing space for the recreation and enjoyment of the people. GAD Loja through agreement with the UTPL , requires a proposal that achieves rescue riverside, in order to maintain and increase its tourism reputation that has taken the Vilcabamba Valley The main idea is propose spaces that do not break with the natural environment , through the use of organic materials form and function that is integrated into its natural context , rescue green areas without any intervention affecting visually, also reforestation areas of identified species is proposed to the Vilcabamba as the Huilco (Anadenanthera colubrine. Brenan) that is vulnerable state of preservation. All this in order that Vilcabamba increase its tourism development. KEYWORDS: